Mobility of Transgenic Nucleic Acids and Proteins within Grafted Rootstocks for Agricultural Improvement - Haroldsen, Victor; Szczerba, Mark W.; Aktas, Hakan; Lopez, Javier; Odias, Mar J.; Chi-Ham, Cecilia L.; Labavitch, John; Bennett, Alan B.; Powell, Ann L. (Frontiers in Plant Science, 2012)
Grafting has been used in agriculture for over 2000 years. Disease resistance and environmental tolerance are highly beneficial traits that can be provided through use of grafting, although the mechanisms, in particular for resistance, have frequently been unknown. As information emerges that describes plant disease resistance mechanisms, the proteins, and nucleic acids that play a critical role in disease management can be expressed in genetically engineered (GE) plant lines. Utilizing transgrafting, the combination of a GE rootstock with a wild-type (WT) scion, or the reverse, has the potential to provide pest and pathogen resistance, impart biotic and abiotic stress tolerance, or increase plant vigor and productivity. Of central importance to these potential benefits is the question of to what extent nucleic acids and proteins are transmitted across a graft junction and whether the movement of these molecules will affect the efficacy of the transgrafting approach. Using a variety of specific examples, this review will report on the movement of organellar DNA, RNAs, and proteins across graft unions. Attention will be specifically drawn to the use of small RNAs and gene silencing within transgrafted plants, with a particular focus on pathogen resistance. The use of GE rootstocks or scions has the potential to extend the horticultural utility of grafting by combining this ancient technique with the molecular strategies of the modern era.